Pengaruh Green Marketing Mix Terhadap Keputusan Pembelian AMDK Le Minerale (Survei pada konsumen Air Mineral Dalam Kemasan Le Minerale di Tasikmalaya) - Siti Ainun Fadilah; Askolani .; Gian Riksa Wibawa (Universitas Dehasen Bengkulu, 2024)
This study aims to determine the simultaneous and partial effects of Green Product, Green Price, Green Place, and Green Promotion variables on Purchasing Decisions. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of Le Minerale Bottled Mineral Water in Tasikmalaya. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis with the help of SPSS 23. The results of this test prove that Green Product, Green Price, Green Place, and Green Promotion simultaneously have a significant effect on purchasing decisions. Green Product partially has no effect on purchasing decisions. Green Price partially has a significant effect on purchasing decisions. Green Place partially has a significant effect on purchasing decisions. Green Promotion partially has a significant effect on purchasing decisions.